Analysis of The Relationship Between Early Life Traumatic Experiences and Vulnerability to Psychosis in Adolescents: A Systematic Review - Ahmad Nasrullah; Irmasanty Irmasanty; Asrini Safitri (CV. AFDIFAL MAJU BERKAH, 2026)
Exposure to traumatic experiences during childhood can cause long-term adverse effects on an individual's psychological and neurobiological development. Psychosis as a severe psychiatric condition characterized by reality distortion often first emerges during adolescent development. This study was conducted using a systematic literature review method through analysis of relevant research articles published between 2015 and 2024. Based on literature analysis, adolescents with a history of childhood trauma show increased vulnerability to psychotic disorders through various mechanisms. Neurobiologically, complex trauma affects the dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, triggers structural brain changes such as reduced hippocampal volume and amygdala enlargement, and disrupts neurotransmitter system balance. From psychological aspects, the formation of maladaptive cognitive schemas, memory disintegration, and deficits in social cognition also contribute to the emergence of psychotic symptoms. This review concludes that there is a significant relationship between past traumatic exposure and increased risk of psychotic disorders in adolescent populations, with a relationship pattern showing dose-response characteristics.